TES INTELEGENSI DAN PEMANFAATANNYA DALAM DUNIA PENDIDIKAN - Rohmah, Umi (Cendekia: Jurnal Kependidikan Dan Kemasyarakatan, 2011)
Success in learning is much more determined by the ability of educators in understanding the diversity of learners, such as the knowledge of the ability of individual learner. By knowing the capabilities of learners, educators will be easily to determine what approaches and methods that appropriate with their need and wish in learning. In this sense, intelligence test and its function in education can not be separated from an understanding of learners. Learners are not merely an exact robot that can be programmed in such way so that they can move under their teachers or parentsâ control. Learners are unique individuals who have their own existence, possess their own soul, and have the right to grow and develop optimally in accordance with the rhythm of each characteristic. Moreover, learners look like various kinds of beautiful flowers in the park who have their own fascination, so it can not be equated or trimmed away equally. They extremely need special and individualized treatment more than just collective treatment.Â Ø§Ø±ØªØ¨Ø· ÙØ¬Ø§Ø Ø§ÙØªØ¹ÙÙÙ â Ø¥ÙÙ ØØ¯ ÙØ§ â Ø¨ÙØ¯Ø±Ø© Ø§ÙÙØ¯Ø±Ø³ Ø¹ÙÙ ÙÙÙ Ø·Ø¨Ø§Ø¦Ø¹ Ø§ÙØ·ÙØ§Ø¨ Ø§ÙÙØªÙÙØ¹Ø© ÙÙÙØ§Ø¡Ø§ØªÙÙ. ÙØ¥Ø°Ø§ Ø¹Ø±Ù Ø§ÙÙØ¯Ø±Ø³ ÙÙØ§Ø¡Ø© ÙÙ Ø·Ø§ÙØ¨ Ø³ÙÙ ÙÙ ÙÙ Ø§Ø®ØªÙØ§Ø± Ø§ÙÙØ¯Ø®Ù ÙØ§ÙØ·Ø±ÙÙØ© Ø§ÙÙÙØ§Ø³Ø¨ÙÙ ÙÙ Ø§ÙØªØ¯Ø±ÙØ³. ÙØ§Ø®ØªØ¨Ø§Ø± Ø§ÙÙÙØ§Ø¡Ø© Ø§ÙÙØ¹Ø±ÙÙØ© ÙØªÙØ¸ÙÙÙØ§ ÙÙ Ø¹Ø§ÙÙ Ø§ÙØªØ±Ø¨ÙØ© ÙØ§ ÙÙÙØµÙ Ø¹Ù Ø§Ø·Ø§Ø± ÙÙÙ Ø·Ø¨Ø§Ø¦Ø¹ Ø§ÙØ·ÙØ§Ø¨. ÙÙÙØ³ Ø§ÙØ·Ø§ÙØ¨ Ø¥ÙØ³Ø§ÙØ§ ÙÙÙØ§ÙÙÙÙØ§ Ø¨ØÙØ« ÙØØ±ÙÙ Ø§ÙÙØ¯Ø±Ø³ ÙÙÙ Ø´Ø§Ø¡. ÙØ§ÙØ·Ø§ÙØ¨ Ø¥ÙØ³Ø§Ù Ø¨ÙØ§ ÙÙ ÙÙ ÙØ²Ø§ÙØ§Ø ÙÙÙ ØÙ Ø£Ù ÙÙÙÙ ÙÙØªØ±ÙÙÙ Ø¨ÙØ§ ÙÙØ§Ø³Ø¨ ÙØ·Ø±ØªÙ Ø§ÙØ®Ø§ØµØ©. ÙÙÙ ÙØ§ÙØ²ÙÙØ± Ø§ÙÙØªÙÙØ¹Ø© ÙÙ ØØ¯ÙÙØ© ÙØ§Ø³Ø¹Ø© Ø ÙÙ ÙÙØ§ ÙØ²Ø§ÙØ§ÙØ§ ÙØ®ØµØ§Ø¦ØµÙØ§ Ø§ÙØªÙ ÙØ§ ÙÙÙÙ ØªØ³ÙÙØªÙØ§ Ù ØªÙØÙØ¯ÙØ§. ØªØØªØ§Ø¬ ÙÙÙ Ø·Ø§ÙØ¨ Ø¥ÙÙ ØªØµØ±Ù ÙÙÂ  Ø®Ø§Øµ Ø¨Ù ÙÙ ÙØ¨Ù Ø§ÙÙØ¯Ø±Ø³.Â